MOTIVASI BELAJAR BIOLOGI SISWA RSBI DAN SISWA REGULER DI SMPN 1 PARIAMAN - Sumarmin, Ramadhan; Anhar, Azwir; Syari, Elsy Melia (IAIN Batusangkar, 2016)
Students are one of the elements involved in the learning process. Student success can not be separated from learning, to improve learning outcomes necessary motivation in learning. Motivation is influenced by multiple factors originating from within is called intrinsic motivation, and students who come from outside the student called extrinsic motivation. The purpose of this research is to know the difference RSBI student motivation to learn biology in junior high school students and regular first Pariaman. Type of research is a descriptive. The population in this research is RSBI students and regular students in junior high school first Pariaman numbering 120 persons. In this study sampling was not done, the entire sampled population. The variables in this research that students' motivation to learn biology RSBI and regular students in junior high school one school year 2009/2010 Pariaman. Data collected by using questionnaire and then analyzed using descriptive analysis of the percentage. Results showed that students' intrinsic motivation to learn in RSBI students higher than regular students. Conversely, the student extrinsic motivation to learn biology in regular students is better than RSBI students. RSBI students' intrinsic motivation in learning biology, including the criteria very well.Key words: Motivation, intrinsic, extrinsic, RSBI